The Effect of Warm Footbath With Salt of Edema Under Extremity In Postpartum Pre Eclamsia - Zakkiyatus Zainiyah; Eny Susanti; Asrifah Asrifah (Universitas Andalas, 2019)
Preeclampsia is a complication of pregnancy that is acute and can occur ante, intra postpartum. Ideally during the postpartum blood pressure 120/80 mmHg. However, based on the preliminary there were 73.9% who experienced lower extremity edema in postpartum preeclampsia. The purpose of this study was to analyze the effect of a warm foot bath with salt edema under extremity in postpartum preeclampsia. The research design was a quasi-experimental pre-post test with control group design. The independent variable was soaking the foot using mixed salt warm water mixed. The dependent variable was extremity edema in the postpartum mother pre-eclampsia. The population was 9 respondents. Samples taken were 9 respondents. The results in the treatment group obtained a value of p = 0.04 while the control group p = 0.05. Test results obtained by Whitney p = 0.004. Based on the results of this study, it is expected that patients with extreme edema in postpartum preeclampsia should be advised to soak the foot using mixed salt warm water to improve blood circulation, especially for sufferers of lower extremity edema in postpartum preeclampsia.